Study of Optimization Planting Patterns of Irrigation Areas Ciujung Ciruas District Using a Linear Program - Rustandi, Rafa Nada; Sejati, Wahyu (Aptisi Transactions On Technopreneurship (ATT), 2022)
Ciujung Irrigation Area (DI) has an area of 21,350 ha. The Ciujung Irrigation Area Irrigation Network is still found to be quite high sedimentation, so that the distribution of water for agricultural needs and other community needs has not been able to be carried out optimally. The purpose of optimizing the planting pattern is to determine the maximum price of the crop that a field with different types of crops can produce. Optimization in this study used a linear program using the POM QM application. In this optimization study, 4 alternatives were planned with 2 different crops, namely corn and peanuts. In the planting pattern, alternative 1 starts planting in December I, alternative 2 starts planting in December II, alternative 3 starts planting in January I, alternative 4 starts planting in January II. The alternative planting pattern chosen is alternative 2 by producing an area of MT I Rice covering an area of 21,350 ha, MT II Rice covering an area of 3671.62 ha, Palawija covering an area of 84.98 ha and the maximum profit obtained in a year is IDR 595,113,300,000